1999
DOI: 10.1136/jnnp.66.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Basilar impression complicating osteogenesis imperfecta type IV: the clinical and neuroradiological findings in four cases

Abstract: Objectives-To describe the clinical and neuroradiological features of basilar impression in patients with osteogenesis imperfecta type IV. Methods-Four patients with basilar impression were ascertained in a population study of osteogenesis imperfecta. All four had detailed clinical and neuroradiological examination with both CT and MRI of the craniocervical junction andposterior fossa structures. Results-All four showed significant compression of the posterior fossa structures and surgical decompression was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 17 publications
1
48
0
3
Order By: Relevance
“…In particular, a reduced sagittal diameter is considered associated with symptoms [20], and measurements less than 30 mm are abnormal [8]. In our case the postmortal breakage prevented measuring the sagittal diameter and therefore it was not possible to argue whether the individual was symptomatic.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, a reduced sagittal diameter is considered associated with symptoms [20], and measurements less than 30 mm are abnormal [8]. In our case the postmortal breakage prevented measuring the sagittal diameter and therefore it was not possible to argue whether the individual was symptomatic.…”
Section: Discussionmentioning
confidence: 97%
“…Chiari malformation is a possible comorbidity. 19,27 Severe pathology can lead to perinatal death, whereas milder forms restrict life and cause moderate reduction of life span. 29 Pathology of the craniocervical junction and cranial base can be divided into 1) basilar impression, characterized by relative lowering of the skull base with endocranial introflection of the posterior edge of the foramen magnum; 2) basilar invagination, where the uppermost cervical structures protrude into the cranium; and 3) platybasia or flattening of the skull base.…”
Section: 25mentioning
confidence: 99%
“…Normal anatomical relations are distorted by bone deformity and the lower surface of the foramen ovale may be posteromedially displaced, thus making the conventional route for percutaneous approaches virtually impossible to use. 5,7,8 The authors found that Mayfield clamps, necessary in the previous alternatives, also imply high complication risk given the potential fragmentation of wormian bones and deformity worsening. In cases of OI, cannulation of the foramen ovale and classical percutaneous treatment can be a useful, safe and efficient alternative using CT-guided puncture for patients with trigeminal neuralgia and other bone deforming diseases that severely affect the skull base.…”
Section: Introductionmentioning
confidence: 99%
“…The upward displacement of the basilar and condylar portions of the occipital bone may cause the foramen magnum to fold inward with subsequent translocation of the upper cervical spine into the brainstem. 7,9 This condition can result in bulbar dysfunction and myelopathy with lower cranial nerve palsies due to stretching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation